Risk analysis and the security survey - Broder, James F. (Butterworth-Heinemann, 2006)
The definitive classic on risk analysis for security and risk assessment professionals!
Includes index.
Keywords: Industries -- Security measures.; Risk management.; Crime prevention surveys.; Assistance in emergencies -- Planning.; Industrie -- Sécurité -- Mesures.; Gestion du risque.; Secours d'urgence -- Planification.; risk management.; TECHNOLOGY & ENGINEERING -- Industrial Health & Safety.; Assistance in emergencies -- Planning; Crime prevention surveys; Industries -- Security measures; Risk management; dissertations.; Academic theses; Academic theses.; Thèses et écrits académiques.